2021
DOI: 10.3389/fgene.2020.614726
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Enolase: Emerging Tumor-Associated Antigen, Cancer Biomarker, and Oncotherapeutic Target

Abstract: Alpha-enolase, also known as enolase-1 (ENO1), is a glycolytic enzyme that “moonlights” as a plasminogen receptor in the cell surface, particularly in tumors, contributing to cancer cell proliferation, migration, invasion, and metastasis. ENO1 also promotes other oncogenic events, including protein-protein interactions that regulate glycolysis, activation of signaling pathways, and resistance to chemotherapy. ENO1 overexpression has been established in a broad range of human cancers and is often associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 97 publications
1
47
0
2
Order By: Relevance
“…Alpha-enolase (ENO1) is a well-studied multifunctional enzyme with a large PPI network consisting of 441 interactors (BioGRID database, ). A pool of recent findings has confirmed a strong relationship between ENO1 overexpression and cancer development [ 148 , 149 ]. ENO1 forms PPIs with EBP and MVK enzymes, with the latter showing a positive correlation of gene expression profiles with ENO1 ( Table 3 ).…”
Section: Discussionmentioning
confidence: 96%
“…Alpha-enolase (ENO1) is a well-studied multifunctional enzyme with a large PPI network consisting of 441 interactors (BioGRID database, ). A pool of recent findings has confirmed a strong relationship between ENO1 overexpression and cancer development [ 148 , 149 ]. ENO1 forms PPIs with EBP and MVK enzymes, with the latter showing a positive correlation of gene expression profiles with ENO1 ( Table 3 ).…”
Section: Discussionmentioning
confidence: 96%
“…It is well established that ENO1 is a metabolic enzyme participating in the synthesis of pyruvate. The upregulation of ENO1 has been reported in BC and is associated with tumor aggression [ 26 ]. ENO1 could be modulated by a variety of mechanisms, such as hypoxic stress, c-MYC, and ERK1/2 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the MS data, the glycolytic enzyme ENO1 piqued our interest. As a well-documented glycolytic enzyme responsible for ATP generation, ENO1 is related to mediate energy metabolism and cancer development [ 11 ]. Recent studies reported that ENO1 was correlated with cancer differentiation and progression in several tumor types by interacting with lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-enolase (ENO1) is an enolase isoform originally characterized as a crucial glycolytic enzyme catalyzing the dehydration of 2-phosphoglycerate into phosphoenolpyruvate; it also generates ATP during glycolysis [ 10 ]. Besides its well-known enzymatic functions, decades of research have shown that ENO1 is aberrantly expressed in multiple tumor types and participates in diverse cellular processes through non-metabolic mechanisms [ 11 ]. Interestingly, some studies reported that lncRNAs interact with ENO1 and affect its expression or activity [ 12 , 13 ], highlighting a novel approach to elucidate the non-metabolic roles of metabolic genes in cancer.…”
Section: Introductionmentioning
confidence: 99%